Thermodynamic understanding the phase behavior of fully quaternized poly(ethylene oxide)-b-poly(4-vinylpyridine) block copolymers. (21st July 2022) - Zhang, Ze-Kun; Ding, Shi-Peng; Ye, Ze; Xia, Ding-Li; Xu, Jun-Ting
Abstract: In this study, the poly(ionic liquid)s (PILs)-based block copolymers (BCPs) with a high charge density, poly(ethylene oxide)- b -quaternized poly(4-vinylpyridinium) with X − as counterion (PEO- b -QP4VP-X), were prepared by full quaternization of the poly(4-vinylpyridine) (P4VP) block in neutral PEO- b -P4VP BCP. The complete quaternization of P4VP block was confirmed by NMR and FT-IR. The phase separation behavior of PEO- b -QP4VP-X BCPs was examined, which was found to be strongly dependent on the counterion species. Specifically, as compared with the neutral PEO- b -P4VP, PEO- b -QP4VP-Br exhibits a stronger segregation strength, while the other three PEO- b -QP4VP-X (X = PF6, TFO and TFSI) BCPs show a weaker phase separation ability. The phase behavior of PEO- b -QP4VP-X was explained using the thermodynamic mechanism originally applied for salt-doped BCPs of low charge density. The variation of the Flory-Huggins parameter (Δ χ ) can be divided into three terms: Δ χ 1 due to the change in monomer identity after quaternization, Δ χ Born from the Born energy of counterions and χ Γ arising from the local charge cohesion. For PEO- b -QP4VP-X BCPs, both Δ χ 1 and Δ χ Born are negative, but χ Γ is positive, and they vary with counterion size in different ways. The competition of these three terms dominates the change tendency of phase behavior, among which Δ χ 1 plays an important role at high level of charge density. The rationality of the aforementioned thermodynamic mechanism of Δ χ was also verified by the phase behavior of salt-doped PEO- b -QP4VP-X. Graphical abstract: Image 1 Highlights: The phase behavior of PEO- b -QP4VP-X BCPs with high charge density is studied. The T DOT of PEO- b -QP4VP-X can be bi-directionally regulated via changing different counterions. The phase behavior of PEO- b -QP4VP-X BCPs is explained from the viewpoint of thermodynamics.